The ADHD toolkit - Wheeler, Linda. 4 0 16; 5 (Los Angeles : SAGE, 2010)
A guide to understanding and supporting students with attention-deficit hyperactivity disorder (ADHD) in schools, providing examples of strategies and activities, advice on working with parents, and related resources, and including case studies, checklists, and more. Includes information to access electronic resource materials online.
PART ONE: BACKGROUND TO ADHD -- The Concept of ADHD -- Use of Medication -- Multiprofessional Involvements -- PART TWO: THE SCHOOL SETTING -- Systematic Classroom Observation -- Effective Teaching for Students with ADHD -- Classroom and Behaviour Management Strategies -- Associated and Co-Existing Difficulties -- PART THREE: THE WIDER CONTEXT -- Working with Parents.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education. -- Attention-deficit-disordered children;Attention-deficit hyperactivity disorder. -- 20; 20; 2